You are on page 1of 54

PRINCIPLES OF CIRCUIT SIMULATION

Lecture 12.
Error Control in
Transient Simulation

Guoyong Shi, PhD


shiguoyong@ic.sjtu.edu.cn
School of Microelectronics
Shanghai Jiao Tong University
Fall 2010

2010-11-19 Slide 1
Outline
• Truncation error
• Local Truncation Error (LTE)
ƒ for FE/BE/TR
• Local error of LMS methods
• Time step control
ƒ Finite difference calculation

2010-11-19 Lecture 12 slide 2


Error Analysis
True solution

Numerical
solution
t

Integration Method Error of


numerical
Round-off errors solution

2010-11-19 Lecture 12 slide 3


Local Error
ƒ Local error is the error that could happen in one
time step Δt, assuming no error at the beginning.

Local Local Local


error error error

Δt Δt Δt

F.E. B.E. T.R.

2010-11-19 Lecture 12 slide 4


Global Error
ƒ Global error is the accumulated error over the
simulation period.
Global
error

Numerical
solution
t

Model errors
Error of
Integration Method numerical
solution
Round-off errors

2010-11-19 Lecture 12 slide 5


Global Truncation Errors
Global Truncation Error (GTE)

Assume initial condition known: x(t0 ) = x0


exact

The error at time point tk+1: ek := x(tk +1 ) − x k +1

No available because the exact solution x(tk+1) is unknown.

2010-11-19 Lecture 12 slide 6


Local Truncation Errors
Local Truncation Error (LTE) (one-step error)

Assume xk is known exactly: x(tk ) = x k (for convenience)

Estimate the error at the next time ek := x(tk +1 ) − x k +1


point tk+1:

• Can be calculated approximately;


• Used to determine the next time step size (Δt) in SPICE

2010-11-19 Lecture 12 slide 7


Dynamic Time Step Control

Numerical
solution

Δt
t
time step
changes

• Dynamic time step control – increase or decrease


time step (Δt) for accuracy control.
• Adopted by most SPICE simulators.
• Typically use Local Truncation Error (LTE).
2010-11-19 Lecture 12 slide 8
Local Truncation Error (LTE)
LTE ≡ One-step error, assuming perfect past data.

LTE := y (t n ) − y n
exact solution simulated

If using a linear multi-step (LMS) method:

perfect past data


k
⎛ m

yn + ∑
i =1
α i y (t n −i ) +hn ⎜ β0 f ( y n ) +



i =1
β i y '(t n −i ) ⎟ = 0


Approximation of y(tn)

2010-11-19 Lecture 12 slide 9


LTE for Typical Methods
• We shall derive the LTE’s of three basic methods
ƒ Forward Euler (FE)
ƒ Backward Euler (BE)
ƒ Trapezoidal Rule (TR)

• The key technique used – Taylor expansion

2010-11-19 Lecture 12 slide 10


Forward Euler (FE)

(exact) (approx)
(exact)

xn
LTE
x (t )
hn

tn t n +1

i
xn , x n are assumed known exactly

2010-11-19 Lecture 12 slide 11


LTE of Forward Euler
i
xn , x n are assumed known exactly

(assume exact)
i
Forward Euler: xn +1 = xn + hn x n x n = x (t n )
• •
x n = x (t n )

i
x (t n ) + hn x (t n ) = xn +1 ≈ x (t n +1 )

x (t ) The error at tn+1 is the LTE:

hn
LTE := x (t n +1 ) − x n +1 = ?
tn t n +1
2010-11-19 Lecture 12 slide 12
LTE of Forward Euler
Taylor expanding x(t) at t = tn+1 :
(assume exact)
• hn2 ••
x (t n +1 ) = x (t n ) + hn x (t n ) + x(t n ) + O(hn3 ) x n = x (t n )
2 • •
x n = x (t n )

⎡ •
⎤ hn ••
2
x (t n +1 ) = ⎢ xn + hn x n ⎥ + x n + O(hn3 )
⎣ ⎦ 2
i hn2 ••
xn +1 = xn + hn x n = xn +1 + x n + O(hn3 )
2
Forward Euler
formula

2010-11-19 Lecture 12 slide 13


LTE of Forward Euler (cont’d)
Ignore the high-
order terms.
0
hn2 •• hn2 ••
LTE := x (t n +1 ) − x n +1 = x n + O (hn ) 3
LTEFE = xn
2 2

LTE

2010-11-19 Lecture 12 slide 14


Backward Euler (BE)

(exact)
(exact)

x (t )
x n +1

LTE

(approx)
hn

tn t n +1

i
xn , x n +1 are assumed known exactly

2010-11-19 Lecture 12 slide 15


LTE of Backward Euler

(assuming) x n = x (t n ) x (t ) = f (x )

x n +1
• •
approx. x n +1 = x (t n +1 ) x (t )
perfect
• hn
xn +1 = xn + hn x n +1
tn t n +1

i
x (t n ) + hn x (t n +1 ) = xn +1 ≈ x (t n +1 )

The error between xn+1 and x(tn+1)


LTE := x (t n +1 ) − x n +1 = ?
2010-11-19 Lecture 12 slide 16
Backward Euler
x n = x (t n )
Taylor expand x(t) at t = tn+1
• •

ii x n +1 = x (t n +1 )
i x (t n +1 )
x (t ) = x (t n +1 ) + x (t n +1 )(t − t n +1 ) + (t − t n +1 )2 + O((t − t n +1 )3 )
2
Evaluate at t = tn :
i hn2 ii
x (t n ) = x (tn +1 ) − hn x (t n +1 ) + x (t n +1 ) + O(hn3 )
2

⎡ •
⎤ hn ••
2
x (t n +1 ) = ⎢ xn + hn x n +1 ⎥ − x (t n +1 ) + O(hn3 )
⎣ ⎦ 2
hn2 ••
• = xn +1 − x (t n +1 ) + O(hn3 )
xn +1 = xn + hn x n +1 2
by B.E.

2010-11-19 Lecture 12 slide 17


Backward Euler (cont’d)
x n = x (t n )
• •
x n +1 = x (t n +1 )
⎡ •
⎤ hn ••
2
x (t n +1 ) = ⎢ xn + hn x n +1 ⎥ − x (t n +1 ) + O(hn3 )
⎣ ⎦ 2
hn2 ••
• = xn +1 − x (t n +1 ) + O(hn3 )
xn +1 = xn + hn x n +1 2
by B.E.

hn2 ••
hn2 ii
LTE := x (t n +1 ) − x n +1 = − x (t n +1 ) + O (hn )
3
LTEBE =− x (t n +1 )
2 2

2010-11-19 Lecture 12 slide 18


Clarification of the Assumption
• x (t n +1 )
x (t n +1 ) = f ( x (t n +1 ) )
assumed known unknown x (t )
x n +1
x(tn+1) will be hn
solved from BE tn t n +1
as xn+1.


xn +1 = x (t n ) + hn x (t n +1 )

2010-11-19 Lecture 12 slide 19


Trapezoidal Rule (TR)
(exact)
(exact) • x (t )

x n +1
xn
LTE

(approx)
hn

tn t n +1

i i
xn , x n , x n +1 are assumed known exactly

2010-11-19 Lecture 12 slide 20


LTE of Trapezoidal Rule (TR)
Assume exactly: x (t )

• • • • hn
x n = x (t n ) x n = x (t n ) x n +1 = x (t n +1 )
tn t n +1

h ⎛• •
⎞ x n +1 := f ( xn +1 )
xn +1 = xn + n ⎜ x n + x n +1 ⎟
2 ⎝ ⎠

h ⎛• •
⎞ The error between xn+1
x (t n ) + n ⎜ n
x ( t ) + x ( t n +1 ⎟ = x n +1 ≈ x (t n +1 )
)
2 ⎝ ⎠ and x(tn+1)?

LTE := x (t n +1 ) − x n +1 = ?
error?

2010-11-19 Lecture 12 slide 21


LTE of T.R.
Taylor expand x(t) at t = tn and evaluate at t = tn+1 :

i hn2 ii hn3 iii


x (t n +1 ) = xn + hn x n + xn + x n + O(hn4 ) hn = t n +1 − t n
2 6

(to be cancelled)
Taylor expand x’(t) at t = tn and evaluate at t = tn+1 :

i i ii hn2 iii
x (t n +1 ) = x n + hn x n + x n + O(hn3 )
2

2010-11-19 Lecture 12 slide 22


LTE of Trapezoidal Rule
hn2 ii hn3 iii
i
x (t n +1 ) = xn + hn x n + xn + x n + O(hn4 ) hn = t n +1 − t n
2 6
i i hn2 iii
ii hn •
x (t n +1 ) = x n + hn x n + x n + O(hn3 ) × x (t n +1 ) = f ( x (t n +1 ), t n +1 )
2 2
ii •
• Eliminate x n to get x n +1 := f ( xn +1 , t n +1 )

⎡• •
⎤ hn iii
3
h
x (t n +1 ) = xn + n ⎢⎣ x n + x (t n +1 ) −
⎥⎦ 12 x n + O( hn )
4

2
hn3 iii
= xn +1 − x n + O(hn4 )
12
by T.R. • •
Assuming x n +1 = x (t n +1 )
h ⎛• •

xn +1 = xn + n ⎜ x n + x n +1 ⎟
2 ⎝ ⎠

2010-11-19 Lecture 12 slide 23


TR LTE (cont’d)
⎡• •
⎤ hn iii
3
h
x (t n +1 ) = xn + n ⎢⎣ x n + x (t n +1 ) −
⎥⎦ 12 x n + O( hn )
4

2
hn3 iii
= xn +1 − x n + O(hn4 )
12

hn3 iii hn3 iii


x (t n +1 ) − xn +1 = − x n + O(hn4 ) LTETR =− xn
12 12

LTE

2010-11-19 Lecture 12 slide 24


PRINCIPLES OF CIRCUIT SIMULATION

LMS Error Analysis

Local error of LMS methods


Error expression of pth order LMS

2010-11-19 Slide 25
Error Analysis of LMS Methods
• We shall compare “local error” and “local truncation
error”:
ƒ Local Error – also known as the Error of the formula (or
called “residue”)
ƒ LTE – One-step Error of the solution

General LMS formula:

k m •
∑α y
i =0
i n −i + hn ∑ β j y n− j = 0, (α0 = 1)
j =0

2010-11-19 Lecture 12 slide 26


LMS Error
General LMS : k m •
∑α y
i =0
i n −i + hn ∑ β j y n− j = 0, (α0 = 1)
j =0

simulated values
(simulated)
If the simulated values are replaced
by the exact values, the LMS formula yn−i ↔ y(tn−i )
might result in “errors”, because the • •
exact solution might not satisfy the y n− j ↔ y(tn− j )
LMS formula.

k m • (exact)
∑α y(t
i =0
i n −i ) + hn ∑ β j y(tn− j ) ≠ 0
j =0

Error
2010-11-19 Lecture 12 slide 27
LMS Local Error
k m •
∑α y(t
i =0
i n −i ) + hn ∑ β j y(tn− j ) ≠ 0
j =0

called “Local Error”

Local Error (LE) is defined as the residue of the LMS formula


with all yi and y’i substituted by their exact values, i.e.
yi = y(ti), y’i = f(y(ti))

k m •
Define:
LE ∑α y(t
i =0
i n −i ) + hn ∑ β j y(tn− j )
j =0

2010-11-19 Lecture 12 slide 28


Local Error (LE) Analysis
Assuming perfect past data:
y (t n − i ) = y n − i for i = 1, 2, ..., k

Solve the current solution yn :

y n ≈ y (t n ) In general, yn is only an
approximation of y(tn).

LTEn := y (t n ) − y n

Question: What is the relation between LE and LTE?

2010-11-19 Lecture 12 slide 29


Local Error (LE) Analysis
k m •
LEn = ∑αi y(tn−i ) + hn ∑ β j y(tn− j )
i =0 j =0

• k m •
= y(tn ) + hn β0 y(tn ) + ∑αi y(tn−i ) + hn ∑ β j y(tn− j )
i =1 j =1

• k m • by
= y(tn ) + hn β0 y(tn ) + ∑αi yn−i + hn ∑ β j y n− j assumption
i =1 j =1

⎡• •
⎤ k m •
LEn = [ y(tn ) − yn ] + hn β0 ⎢ y(tn ) − y n ⎥ + ∑αi yn−i + hn ∑ β j y n− j
⎣ ⎦ i =0 j =0

Note the index change !


2010-11-19 Lecture 12 slide 30
Local Error (LE)
⎡• •
⎤ k m •
LEn = [ y(tn ) − yn ] + hn β0 ⎢ y(tn ) − y n ⎥ + ∑αi yn−i + hn ∑ β j y n− j
⎣ ⎦ i =0 j =0

⎡i i

LE = [ y (t n ) − y n ] + hn β0 ⎢ y (t n ) − y n ⎥
⎣ ⎦ = 0 by LMS
definition
⎡ i

= [ y (t n ) − y n ] + hn β0 ⎢f ( y (t n ) ) − y n ⎥
⎣ ⎦
= LTE
LTE = 0 Î LE = 0 (easy to see)

i i
LTE = y (t n ) − y n = 0 f ( y (t n )) − y n = f ( y (t n )) − y (t n ) = 0

What about the converse: LE = 0 Î LTE = 0 ?


2010-11-19 Lecture 12 slide 31
LTE versus LE
LTE y (t n ) − y n
⎡i ⎤
LE = ⎡⎣ y (t n ) − y n ⎤⎦ +h n β 0 ⎢ y (t n ) - f ( y n ) ⎥
⎣ ⎦
⎡i ⎤
LTE = −h n β 0 ⎢ y (t n ) - f ( y n ) ⎥ + LE
⎣ ⎦
= −h n β 0 ⎣⎡f ( y (t n ) ) - f ( y n ) ⎦⎤ + LE

We have to assume that f(·) is “Lipschitz” in order to derive a


bound for the “LTE” in terms of “LE”.

2010-11-19 Lecture 12 slide 32


Lipschitz Condition
• A function y = f(x) is Lipschitz if the variation of y can
be “linearly bounded” by the variation of x.

y = f ( x)

f (x 1 ) − f (x 2 ) ≤ L x 1 − x 2

L is called a Lipshitz constant.

2010-11-19 Lecture 12 slide 33


LTE Bound by LE
LTE = y ( t n ) − y n
≤ hn β 0 f ( y ( t n ) ) - f ( y n ) + LE
≤ hn β 0 L y ( t n ) − y n + LE
≤ hn β 0 L LTE + LE

L is the Lipschitz constant for f(x)


for hn = h
f (x 1 ) − f (x 2 ) ≤ L x 1 − x 2

LE
LTE ≤ If L is large, choose h small
1 − h β0 L
to get a valid bound.

2010-11-19 Lecture 12 slide 34


Taylor Analysis of Local Error
k m

∑ α y (t ∑β

L E = E [ y ( t ), h ] : = i n −i )+ h i y (tn −i )
i =0 i =0

Suppose y(t) is smooth. Its Taylor expansion at t = tn


y ( p +1) (t n )
y (t ) = y (t n ) + y (t n )(t − t n ) + ... +
(1 )
(t − t n )p +1 + ...
( p + 1)!
= q p ( t ) + rp ( t )
remainder

y (p+1) (t n )
p rp (t) = (t − t n ) p +1 + ...
y (i ) (t n ) (p + 1)!
q p (t ) = ∑ (t − t n )i
i =0 i! = O ((t − t n ) p +1 )
(polynomial part) for the remainder
2010-11-19 Lecture 12 slide 35
Analytical Expression for LE
linear
k m

∑ α y (t ∑β

L E = E [ y ( t ) , h ] := i n−i )+ h i y (tn −i )
i =0 i =0

plug in
y (t ) = q p (t ) + r p (t )

p
y (i ) (t n )
pth order polynomial: q p (t ) = ∑ i ! (t − t n )
i

i =0

y ( p +1) (t n )
remainder: r p (t ) =
( p + 1)!
(
(t − t n ) p +1 + O (t − t n ) p + 2 )

2010-11-19 Lecture 12 slide 36


Analytical Expression for LE
Assume the LMS is a pth order method; namely, it is exact
for any pth order polynomials.
0
LE = E ⎡⎣q p (t ), h ⎤⎦ + E ⎡⎣r p (t ), h ⎤⎦
k
⎡ y ( p +1) (t n ) p +1 ⎤
m
y ( p +1) (t n )
= ∑ ⎢α i ( n −i n ) ⎥ ∑ i ( n −i n )
p
t − t + h β t − t
i =0 ⎣ ( p + 1)! ⎦ i =1 p !
+ O (h p +2 )

Terms from the remainder of y(t)

⎡ y ( p +1) (t n ) ⎤
y (t ) = y (t n ) + y (t n )(t − t n ) + ... + ⎢
(1 )
(t − t n )p +1 ⎥ + ...
⎣ ( p + 1)! ⎦
2010-11-19 Lecture 12 slide 37
Analytical Expression for Local Error
LE = E ⎡⎣r p (t ), h ⎤⎦
k
⎡α i y ( p +1) (t n ) p +1 ⎤
m
⎛ h βi y ( p +1) (t n ) p ⎞
= ∑⎢ (t n −i − t n ) ⎥ + ∑ ⎜ (t n −i − t n ) ⎟ + O (h p +2 )
i =0 ⎣ ( p + 1)! ⎦ i =1 ⎝ p! ⎠
k ⎡ p +1 p
⎛ t n −i − t n ⎞ ⎤ m ⎡
⎛ t n −i − t n ⎞ ⎤ y
( p +1)
(t n ) p +1
= ∑ ⎢α i ⎜ ⎟ ⎥ + ( p + 1) ∑ ⎢ β i ⎜ ⎟ ⎥ h + O (h p + 2 )
i =0 ⎣⎢ ⎝ h ⎠ ⎦⎥ ⎢ ⎝
i =1 ⎣ h ⎠ ⎦⎥ ( p + 1)!
= ε p +1y ( p +1) (t n )h p +1 +
High Order Terms
coefficient
O(hp+1)

⎡ p +1 p
⎛ t n −i − t n ⎞ ⎤ 1
k
⎛ t n −i − t n ⎞
ε p +1 ∑ ⎢α i
i =0 ⎢

⎝ h ⎟

+ ( p + 1) βi ⎜
⎝ h ⎟ ⎥
⎠ ⎥⎦ ( p + 1)!

for any method of order p


2010-11-19 Lecture 12 slide 38
Expression for Local Error
p +1 p
1 ⎧⎪ k ⎛ t n −i − t n ⎞ m
⎛ t n −i − t n ⎞ ⎫⎪
ε p +1 ⎨∑ α ⎜ h ⎟ + ( p + 1)∑ βi ⎜ ⎟ ⎬
( p + 1)! ⎩⎪ i =1 i ⎝ ⎠ i =1 ⎝ h ⎠ ⎭⎪

h = t n − t n −1 time stepsize

1 k
1 m
∑ ( ) ∑ ( )
p +1 p
ε p +1 −i α i + −i βi
( p + 1)! i=1 p ! i= 1

Coefficient of the local error (LE)

LE = E ⎡⎣r p (t ), h ⎤⎦ = ε p +1 y ( p +1) (t n )h p +1 +
(for a pth order LMS)
2010-11-19 Lecture 12 slide 39
LE Examples
Applying the analytical LE expression to some basic
integration methods:

• Forward Euler
• Backward Euler
• Trapezoidal Rule
• Gear Integration Formulas

2010-11-19 Lecture 12 slide 40


LE of Forward Euler
1 k
1 m
∑ ( ) ∑ ( )
p +1 p
ε p +1 −i α i + −i βi
( p + 1)! i=1 p ! i=1

F.E. : α0 = 1, α1 = -1, β0 = 0, β1 = -1 Î Order of method p = 1

ε2 = [ (-1)(-1)2 - 2(-1) ] /2 = 1/2 Coefficient of LE

ii
1 ii
LE = E [r1 (t ), h ] = ε 2 y (t n )h = y (t n )h 2
2
(Same result as the
2 LTE analysis)

2010-11-19 Lecture 12 slide 41


LE of Backward Euler
1 k
1 m
∑ ( ) ∑ ( )
p +1 p
ε p +1 −i α i + −i βi
( p + 1)! i=1 p ! i=1

B.E. : α0=1, α1=-1, β0=-1, β1=0 Î Order of method p = 1

ε2 = [ (-1)(-1)2 ] /2= -1/2 Coefficient of LE

2010-11-19 Lecture 12 slide 42


LE of Trapezoidal Rule
1 k
1 m
∑ ( ) ∑ ( )
p +1 p
ε p +1 −i α i + −i βi
( p + 1)! i=1 p ! i=1

T.R. : α0=1, α1=-1, β0=-1/2, β1=-1/2 Î Order of method p = 2

ε3 = [(-1)(-1)3 - (3/2) (-1)2] /3! = -1/12 Coefficient of LE

2010-11-19 Lecture 12 slide 43


LE of Gear’s Formula
• k
1
Gear’s formula (kth order): yn = −
β h
0
∑ αy
i =0
i n −i

k
The coefficient equations:
∑ (i
i =0
q
)α i − ( q i0 q −1 )β0 = 0; q = 0,1, , k

Truncation error coefficient:


1 k

∑ ( )
k +1
ε k +1 −i αi
(k + 1)! i=1

2010-11-19 Lecture 12 slide 44


Examples (Gear Coefficients)
1st order Gear (Backward Euler) k=1

α0 = 1 ⎧α 0 + α1 = 0
⎨ α1 = −1, β0 = −1,
⎩α1 = β0
α1 1
ε2 = =−
2nd order Gear k=2 2! 2

⎧α 0 + α1 + α 2 = 0,
α0 = 1 ⎪ 4 1 2
⎨α1 + 2α 2 = β0 , α1 = − , α 2 = , β0 = − ,
⎪α + 4α = 0. 3 3 3
⎩ 1 2

α1 + 2 3 α 2 2
ε3 = = = 0.222222
3! 9
2010-11-19 Lecture 12 slide 45
Gear Coefficients
3rd order Gear k=3 3 •
∑α y
i =0
i n −i + h β0 y n = 0
Coef. eqn.:
α0 = 1
⎧α1 + α 2 + α 3 = −1, 18 9 2
⎪ α1 = − , α2 = , α3 = − ,
⎪α1 + 2α 2 + 2α 3 = β0 , 11 11 11
⎨ 6
⎪α1 + 4α 2 + 9α 3 = 0, β0 = − ,
11
⎪⎩α1 + 8α 2 + 27α 3 = 0.

1 k

∑ ( ) αi
k +1
ε k +1 −i
(k + 1)! i=1
α1 + 2 4 α 2 + 3 4 α 3 3
ε4 = =− = −0.1363636
4! 22
2010-11-19 Lecture 12 slide 46
PRINCIPLES OF CIRCUIT SIMULATION

Time Step Control

Calculation of Finite Difference

2010-11-19 Slide 47
Time Step Control
• Let E be the allowed LTE bound at any time point.

LTE (t n ) ≤ E

• Then the time step bound for the TR is calculated


as
1
3 iii ⎛ ⎞ 3
h n
xn ≤ E hn ≤ ⎜12E iii ⎟
⎜ | ⎟⎠
12 ⎝ | xn

We need to calculate the high-


hn3 iii
LTETR (t n ) = − xn order derivative approximately
12 by finite differences.
2010-11-19 Lecture 12 slide 48
Finite Difference Calculation
• Let Δk(tn) be the kth order finite difference (FD) at tn.
• It can be calculated by recursive formulas using the
past data.

xn − xn −1
1st order FD: Δ x (t n ) = hn = t n − t n −1
hn

xn −1 xn
2nd order FD: Δ x (t n ) − Δ x (t n −1 )
Δ 2 x (t n ) ≈
hn xn − 2

hn −1 hn
Higher-order FD computation will tn −2 t n −1 tn
have to use polynomial interpolation.

2010-11-19 Lecture 12 slide 49


FD Calculation (cont’d)
High-order finite-differences with varying time-steps:

p −1 p −1
Δ x ( t ) − Δ x (t n −1 ) Derived from Lagrange
Δ p x (t n ) = n
(t n − t n − p )( p − 1) p p≥2
interpolation (details
omitted).
(approximated by)

Δ p −1 x (t n ) − Δ p−1 x (tn −1 ) Δ p −1 x (t n ) − Δ p−1 x (tn −1 )


Δ p x (t n ) ≈ OR Δ x (t n ) ≈
p

(hn + hn −1 + + hn − p −2 ) ( p − 1)hn

Implemented in Spice3f5. * These formulas are equivalent


for the case of uniform time step.

2010-11-19 Lecture 12 slide 50


LTE for C with B.E.
• With Backward Euler, the LTE’s for capacitances (C)
is given by

dv d 2 v 1 di ••
1 i(tn+1 ) − i(tn )
i=C 2
= v (t n ) =
dt dt C dt C hn

hn2 •• hn2 •• h
LTEBE =− xn LTEBE = v n = n i (t n +1 ) − i (t n ) ≤ EC
2 2 2C

2C
Δt n ≤ EC
iC (t n +1 ) − iC (t n )

EC is the LTE bound


for C Δt n = t n +1 − t n = hn
2010-11-19 Lecture 12 slide 51
LTE for L with B.E.
• By Backward Euler, the LTE for inductances (L) is
given by

di d 2 i 1 dv ••
1 v(tn+1 ) − v(tn )
v =L 2
= i (t n ) =
dt dt L dt L hn

hn2 •• hn2 •• h
LTEBE =− xn LTEBE = i n = n v (t n +1 ) − v (tn ) ≤ EL
2 2 2L

2L
Δt n ≤ EL
v L (t n +1 ) − v L (t n )

EL is the LTE bound Δt n = t n +1 − t n = hn

2010-11-19 Lecture 12 slide 52


Student Implementations
peak
without LTE with LTE
peak
tail tail

Implementation by XU Hui HSPICE


(class 2008) tail

2010-11-19 Lecture 12 slide 53


Acknowledgement
• Some slides are adapted from
ƒ Prof. Albert Sangiovanni-Vincentelli’s lecture at University of
California, Berkeley (instructor Alessandra Nardi)
ƒ Prof. C.-K. Cheng’s lecture at University of California at San
Diego

2010-11-19 Lecture 12 slide 54

You might also like